On the Nachbin compactification of products of totally ordered spaces - D. C. Kent; Dongmei Liu; T. A. Richmond (International Journal of Mathematics and Mathematical Sciences)
Necessary and sufficient conditions are given for β0(X×Y)=β0X×β0Y, where X and Y are totally ordered spaces and β0X denotes the Nachbin (or Stone-Čech ordered) compactification of X.